Perbaikan Kualitas Citra Digital Menggunakan Metode Kervel Konvolusi - Rambe, Rosmaida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Image processing (digital image processing) is a discipline that studies image processing techniques. The image referred to in this study is a static image originating from the vision sensor (webcame). Mathematically, image is a continuous function with light intensity in a two-dimensional plane. So that it can be processed with a digital computer. An image must be represented numerically with discrete values. A digital image can be represented by a two-dimensional matrix f (x, y) consisting of M columns and N rows. In this study, the color model used is the HSV color model, namely the image (RGB) is converted into HSV to determine the comparison of the original image with the conversion results from RGB to HSV. In image color processing, there are various models, one of which is the hue, saturation, value (HSV) model. By using this model, an object with a certain color can be detected and reduce the influence of the light intensity from outside. The search for paint color codes serves to facilitate all the work of buyers and sellers in determining the color of paint to be taken so that sellers and buyers no longer have to use a catalog to determine paint color and paint code. Image processing (digital image processing) is a discipline that studies image processing techniques. The image referred to in this study is a static image originating from the vision sensor (webcame). Mathematically, image is a continuous function with light intensity in a two-dimensional plane. So that it can be processed with a digital computer. An image must be represented numerically with discrete values. A digital image can be represented by a two-dimensional matrix f (x, y) consisting of M columns and N rows. In this study, the color model used is the HSV color model, namely the image (RGB) is converted into HSV to determine the comparison of the original image with the conversion results from RGB to HSV. In image color processing, there are various models, one of which is the hue, saturation, value (HSV) model. By using this model, an object with a certain color can be detected and reduce the influence of the light intensity from outside. The search for paint color codes serves to facilitate all the work of buyers and sellers in determining the color of paint to be taken so that sellers and buyers no longer have to use a catalog to determine paint color and paint code.